Design and development of rectangular patch antenna with superstrates for the application in portable wireless equipments and aircraft radome. Issue 4 (April 2014) - Biswas, Manotosh; Sen, M.
ABSTRACT This article presents a set of CAD oriented closed form expressions to predict accurately the effect of radome (superstrate) on resonant frequency, input impedance, bandwidth, and gain of rectangular patch antenna. Merits of this model include low computation cost and mathematical simplicity. The numerical values obtained with the present method are compared with experimental and different theoretical values. The accuracy of this model is verified with electromagnetic software (HFSS) computation and with the experimental values. The present model shows very close agreements with the experimental and software computation values compared to the other models for wide range of thickness and permittivity of substrates and superstrates. This model is directly applicable for the integration of patch antennas beneath plastic covers or protective superstrates in portable wireless equipment and aircraft radome. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:883–893, 2014